2015
DOI: 10.1142/s0219887815500528
|View full text |Cite
|
Sign up to set email alerts
|

Moving non-null curves according to Bishop frame in Minkowski 3-space

Abstract: In this paper, we introduce three new transformations and establish connections between moving non-null curves and soliton equations according to Bishop frame in Minkowski 3-space. Later we find formulas for differentials of these three new transformations associated with the nonlinear heat system and repulsive type nonlinear Schrödinger equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 17 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Gürbüz [48] concluded that if the flow of the curve 𝛼(s, u) is governed by the Landau-Lifshitz equation, which is given by ( 1 ) t =  1 ×  ( 1 ) ss , then the kinematics of the spacelike evolving curve 𝛼(s, u) are written by 𝜕 𝜕s…”
Section: Third Class Of Spacelike Pseudo-solitonic Magnetic Curves Co...mentioning
confidence: 99%
“…Gürbüz [48] concluded that if the flow of the curve 𝛼(s, u) is governed by the Landau-Lifshitz equation, which is given by ( 1 ) t =  1 ×  ( 1 ) ss , then the kinematics of the spacelike evolving curve 𝛼(s, u) are written by 𝜕 𝜕s…”
Section: Third Class Of Spacelike Pseudo-solitonic Magnetic Curves Co...mentioning
confidence: 99%
“…Recently, some geometers studied connections between moving frame of space curves and soliton equations in ambient spaces (see [4][5][6][7][8][9][10][11][12][13]).…”
Section: Introductionmentioning
confidence: 99%
“…The differential formulas of Hasimoto transformations in Euclidean 3-space have been presented by Langer and Perline [4]. For the extension to the Lorentz version, Gürbüz suggested three classes of curve evolution associated with the nonlinear Schrödinger equation in Minkowski 3-space (see [6,8,9,12]). Also, Gürbüz [6] extended the results of Langer and Perline in [4] in Minkowski 3-space, and she derived differential formulas of Hasimoto transformations for the first class of curve evolutions associated with the repulsive-type nonlinear Schrödinger equation in Minkowski 3-space.…”
Section: Introductionmentioning
confidence: 99%
“…Munijara and Lakshmanan investigated the motion of space curves in a three-dimensional Minkowski space [20]. Gürbüz studied three classes of curve evolution in terms of Bishop frame in Minkowski 3-space [10]. Guha studied the connection of moving space curves with KdV-type equations in Euclidean 3-space [9].…”
Section: Introductionmentioning
confidence: 99%